Dexamethasone (DXM)‐Coated Poly(lactic‐co‐glycolic acid) (PLGA) Microneedles as an Improved Drug Delivery System for Intracochlear Biodegradable Devices (Adv. Therap. 11/2021). Issue 11 (18th November 2021) - Pawley, Devon C.; Goncalves, Stefania; Bas, Esperanza; Dikici, Emre; Deo, Sapna K.; Daunert, Sylvia; Telischi, Fred
Abstract : In article 2100155, Sylvia Daunert, Fred Telisch, and co‐workers have demonstrated that biodegradable polymers such as poly[lactic‐co‐glycolic] acid can be successfully used to deliver dexamethasone, a corticostereoid, into the cochlea to combat hair cell death. The use of microneedles that are made of PLGA we can address the hinderances caused by the cochlear anatomy but also propose a new methodology that can be applied to other areas of the anatomy that requires sustained and uniform drug delivery.